New strategies to prevent transplant rejection: from molecules to mice to monkeys to man - Larsen, Christian (Henry Stewart Talks, 2007)
Clinical transplantation, Current immunosuppression, T-cell activation, Co-stimulatory pathways, CD28 pathway, Mechanisms of action and clinical development, CD40-CD154 pathway
Archived at 2018/12/10